Endovascular treatment of nonfunctional vascular access through retrograde arterial access: A single-center experience with midterm follow-up - Öğüşlü, Umut; Gümüş, Burçak (Journal of Surgery and Medicine, 2022)
Background/Aim: Nonfunctional vascular access is treated through venous or brachial artery access traditionally. However, each route has its drawbacks. This study aimed to evaluate the feasibility, safety, and effectiveness of retrograde arterial access (RAA) in the treatment of nonfunctional vascular access with mid-term results. Methods: Patients with nonfunctional vascular access who were treated through RAA between January 2019 and December 2020 were included in this cohort study. Patient demographics, lesion characteristics, procedural details, technical and clinical outcomes were noted. Results: Thirty-six interventions were performed on 30 patients. Twenty-nine occlusions and seven long segment stenoses were treated. The radial artery was accessed in 34 cases, the interosseous and ulnar arteries were accessed in one case each. The technical and clinical success rates were 100% and 97.2%, respectively (35/36). Venous rupture was encountered in three patients. No puncture-site complication was observed. The mean follow-up time was 14.3 (range: 6-24) months. None of the patients showed signs of hand ischemia and the accessed arteries were patent at Color Doppler Ultrasound examinations. Post-intervention primary patency rates were 100%, 73.3%, 47.5% at 1, 6 and 12 months, respectively. Post-intervention secondary patency rates were 100%, 93.3%, 84.8% at 1, 6 and 12 months, respectively. Conclusion: RAA is effective and safe in the treatment of nonfunctional vascular access with comparable outcomes to traditional routes. The low access-site complication rates make this access site an attractive salvage route when traditional approaches are not feasible.